Single-molecule junctions based on bipyridine: impact of an unusual reorganization on charge transport - Bâldea, Ioan (The journal of physical chemistry. C, Energy, materials, and catalysis, 2014)
The (4,4′)-bipyridine molecule (44bpy) has attracted particular interest in molecular electronics because single-molecule junctions can be directly formed via nitrogen-gold affinity, obviating the need of understanding nontrivial invasive effects due to extra anchoring groups. In a recent study, an apparent conundrum related to the transport through 44bpy junctions has been resolved by emphasizing the essential role of the environment (solvent vs ambient conditions). In the present paper, we demonstrate the robustness of the conclusion of that study, by introducing intramolecular reorganization as a new and essential element in the analysis.